Legal financial obligations: a focal concerns perspective - Parks, Megan, author; Nowacki, Jeffrey, advisor; Unnithan, Prabha, committee member; Hughes, Shannon, committee member (Colorado State University. Libraries, 2019)
Using State Court Processing Statistics (SCPS) data from 2009, I examine the effects of personal characteristics on the amount of legal financial obligations (LFOs) imposed on defendants and the monetary amount of these LFOs. Drawing on focal concerns theory, first developed by Steffensmeier (1980), which identifies three factors used by court actors in criminal sentencing: blameworthiness of the offender, protection of community, and practical constraints and consequences. Adjusting to these practical constraints causes court actors to employ "perceptual shorthand", utilizing defendant's characteristics in sentencing decisions. Applying focal concerns perspective is a novel approach to evaluating the effect of race/ethnicity, age, and gender on LFO imposition and LFO amounts.